Elevation of serum human epididymis protein 4 (HE4) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) as predicting factors for the occurrence of acute kidney injury on chronic kidney disease: a single-center retrospective self-control study - Song, Jinye; Chen, Ling; Yuan, Zheping; Gong, Xuezhong (Frontiers in Pharmacology, 2023)
Objectives: To evaluate whether novel biomarkers of renal injury, serum HE4 and NT-proBNP could predict acute kidney injury (AKI) on chronic kidney disease (CKD) (A on C) and assess the specificity and efficiency of serum creatinine (SCr), HE4 and NT-proBNP in identifying potential AKI. Meanwhile, the potential early-warning value of HE4 and NT-proBNP in CKD patients was explored.We performed a single-center, retrospective cohort study of 187 adult CKD patients. 32 AKI (grades 1-2) patients with pre-existing CKD (stages 3-5) were Group 1, 59 patients of CKD (stages 4-5) were Group 2. Another 96 patients of CKD (stages 1-3) were Group 3. All patients received general treatments, Group 1 patients received Chinese herb formulation (Chuan Huang Fang-Ⅱ) simultaneously. These 155 CKD (stages 1-5) without AKI patients were observed for descriptive analysis.Results: HE4 in Group 1 (860.63 ± 385.40) was higher than that in Group 2 (673.86 ± 283.58) before treatments. BUN, SCr, UA, NGAL, IL18, HE4 and NT-proBNP in Group 1 were lower, while eGFR was higher (p < 0.01, after v.s. before treatments). In Group 1, both HE4 and NT-proBNP were positively correlated with SCr (respectively r = 0.549, 0.464) before treatments. The diagnostic performance of serum HE4 and NT-proBNP for A on C was 351.5 pmol/L, 274.5 pg/mL as the optimal cutoff value (Area Under Curve (AUC) 0.860 (95% CI: 0.808 -0.913, p < 0.001), (AUC 0.775 (95% CI: 0.697 -0.853, p < 0.001), with a sensitivity and specificity of 100% and 66.5%, 87.5% and 48.8%, respectively). In Group 2, serum HE4 was correlated with SCr (r = 0.682, p < 0.01) before treatments. Serum HE4 and NT-proBNP were elevated in advanced CKD stages, and were increased as CKD stages progressed with statistical significance.: This work indicated serum HE4 and NT-proBNP should elevate in A on C and CKD patients, HE4 is positively correlated with the disease severity, and patients with higher HE4 and NT-proBNP usually have poorer prognosis. Thus, serum HE4 and NT-proBNP are impactful predictors of A on C. Additionally, serum HE4 and NT-proBNP have the potential to evaluate clinical efficacy of A on C.